Work situation and quality of life of call center employees - Medina, Ma. Lilet Cruz; Gabriel, Florenda S. (2008.)
This study sought to describe the work situation and quality of life of call center employees. The survey design was used for the research. Ninety call center agents from four call center agencies participated in the survey. The survey instrument consisted of rating scales to measure the work condition as well as the quality of life of the respondents. Findings revealed that call center employees indicated fair working conditions in the physical, mental, social and emotional areas. They reported several work-related problems, with the most prevalent problems coming from the physical dimension like appetite and weight change. Call center employees were regularly stressed by various stressors like health, work, emotional and general well-being. Even though employees often experienced health-related work problems and were regularly stressed, very few call center agencies offered health programs as well as stress management programs for their employees. Respondents reported poor quality of life in the physical, mental and social areas while emotional quality of life received a moderate rating. They often experience poor diet, fatigue, sleeping difficulties and worries. Most call center employees perceived a worsening quality of life. The respondents also felt dissatisfied with several areas of their life including their job, physical health, mental health, personal life, and handling of problems. Spearman rho correlation showed that there was a significant positive relationship between work condition and quality of life.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Call centers -- Philippines -- Employeees; Call centers -- Employees -- Quality of life